Hematological Parameters and Indices Reference Interval in Pediatric Egyptian Population; A Single Institution Experience - Mansour, Iman; El Zayat, Susan; Karas, Sandra; Arafat, Aya (Open Access Macedonian Journal of Medical Sciences, 2022)
OBJECTIVE: Differentiating a health from a non-health state requires meticulous knowledge of the reference interval (RI). Over the past years, numerous working groups generated ethnic, age, and gender tailored RI in all laboratory tests. The paucity of regional studies covering the normal hemogram values resulted in the adoption of the western population RI which is influenced by ethnic and geographical differences. AIM: The current study, aimed at generating the Egyptian pediatric group hemogram RI. SUBJECTS AND METHODS: At Abu-Rish Japanese hospital, Cairo University Specialized Pediatric Hospital, the study included 1099 Egyptian surgical patients, of both sexes, with an age range between 1-month and 144 months. The electronic peripheral blood count test results archived in the laboratory information system were collected from January 2006 to December 2017 followed by a non-parametrical comparative study to compute the consecutive age groups for generation of continuous indirect RI (2.5th and 97.5th percentiles). RESULTS: The age clusters, 2–5 months, 6–11 months 12–23 months, 24–59 months, and 60–144 months, were created based on hemoglobin (Hb), Red blood cells count, and platelet count data. CONCLUSION: Previously published pediatric hemogram, Western and African-based, RIs show great variation. The comparative study of Hb between each month of life created different consecutive age groups than those adopted by Western countries and other African countries. The Hb results within each group showed substantial differences, between the RI of the western countries and those of Egyptian subjects specifically a lower limit of anemia diagnosis as well as a lower limit of leucopenia diagnosis. The age-specific RI we propose would change the threshold for anemia, and leucopenia diagnosis. The results might justify the use of national RI, after its validation, instead of the international ones.